Political competition and legislative shirking in roll-call votes: Evidence from Germany for 1953–2017 - Marco Frank; David Stadelmann (Public Choice, 2021)
We analyze the impact of elected competitors from the same constituency on legislative shirking in the German Bundestag from 1953 to 2017. The German electoral system ensures at least one federal legislator per constituency with a varying number of elected competitors between zero to four from the same constituency. We exploit the exogenous variation in elected competitors by investigating changes in competition induced by legislators who leave parliament during the legislative period and their respective replacement candidates in an instrumental variables setting with legislator fixed effects. The existence of elected competitors from the same constituency reduces absentee rates in roll-call votes by about 6.1 percentage points, which corresponds to almost half of the mean absentee rate in our sample. The effect is robust to the inclusion of other measures of political competition.
Keywords: D72; D78; H11; 330; Political competition; Accountability; Absence; Rent seeking; Political representation